2018
DOI: 10.1186/s12199-018-0699-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-embedded materials effectively remove hexavalent chromium (CrVI) from aqueous solution

Abstract: BackgroundCurrently, it is recognized that water polluted with toxic heavy metal ions may cause serious effects on human health. Therefore, the development of new materials for effective removal of heavy metal ions from water is still a widely important area. Melanin is being considered as a potential material for removal of heavy metal from water.MethodsIn this study, we synthesized two melanin-embedded beads from two different melanin powder sources and named IMB (Isolated Melanin Bead originated from squid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…The toxicity level of hexavalent chromium (IV) (Cr 6+ ) is higher relative to trivalent chromium (Cr 3+ ). In addition, Cr 6+ is believed to become reduced into Cr 3+ in the human body [ 26 , 60 ]. Evidence for the carcinogenicity of Cr 3+ in humans is lacking, but it could cause skin rashes [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity level of hexavalent chromium (IV) (Cr 6+ ) is higher relative to trivalent chromium (Cr 3+ ). In addition, Cr 6+ is believed to become reduced into Cr 3+ in the human body [ 26 , 60 ]. Evidence for the carcinogenicity of Cr 3+ in humans is lacking, but it could cause skin rashes [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Melanin was extracted from Splendid Squid (Loligo formosana) as reported in our previous study (Cuong et al 2018). Commercial feed in the bead form with a diameter of 2 mm (containing 45-50% starch) was used as the core feed to produce melanin-containing feedstuffs with different formulas.…”
Section: Preparation Of Melanin-containing Feedstuffsmentioning
confidence: 99%
“…Melanin is a natural polymer with very low toxicity (Garcia Borron et al 2014). Melanin has many important roles in the human body including UV-radiation absorbent (Brenner and Hearing 2008), antioxidant (Vate and Benjakul 2013), and heavy-metal absorbent properties (Cuong et al 2018). Melanization and melanin secretion help shrimp protect themselves by encapsulating pathogens and excreting them into the environment (Charoensapsri et al 2014;Sutthangkul et al 2015;Harikrishnan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[15]. 3C + 2Cr2O7 2-+ 16H + →4Cr 3+ + 3CO2 + 8H2O (9) The above three factors exerted different influences on the removal efficiency. This study also delved into the effects of adsorption under different environmental conditions through a four-level orthogonal test on the four factors.…”
Section: Influences Of Ph Adsorbent Dose and Temperaturementioning
confidence: 99%
“…Many authors have reported on the ability of different methods to remove Cr(VI) including adsorption, electrocoagulation, ion exchange, chemical precipitation, membrane separation, reduction, and biosorption methods [5][6][7]. Adsorption is considered as a simple, highly efficient [8], and low-cost method [9]. As such, many studies have been performed on adsorbents used in sewage treatments [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%